2022
DOI: 10.3389/fphar.2022.832299
|View full text |Cite
|
Sign up to set email alerts
|

Using network pharmacology to explore the mechanism of Danggui-Shaoyao-San in the treatment of diabetic kidney disease

Abstract: Danggui-Shaoyao-San (DSS) is one of traditional Chinese medicine, which recently was found to play a protective role in diabetic kidney disease (DKD). However, the pharmacological mechanisms of DSS remain obscure. This study would explore the molecular mechanisms and bioactive ingredients of DSS in the treatment of DKD through network pharmacology. The potential target genes of DKD were obtained through OMIM database, the DigSee database and the DisGeNET database. DSS-related targets were acquired from the BAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
(52 reference statements)
1
1
0
Order By: Relevance
“…Hyperglycemia is known to induce synaptic dysfunction and disrupt the balance of neurotransmitter secretion ( 47 ). Furthermore, differential gene expression analyses in various diabetic tissues were similar to our findings, with overlapping pathways observed in skeletal muscle ( 48 ), β-cell-enriched tissue ( 49 ), diabetic kidney ( 50 , 51 ), and diabetic peripheral neuropathy ( 52 ).…”
Section: Discussionsupporting
confidence: 87%
“…Hyperglycemia is known to induce synaptic dysfunction and disrupt the balance of neurotransmitter secretion ( 47 ). Furthermore, differential gene expression analyses in various diabetic tissues were similar to our findings, with overlapping pathways observed in skeletal muscle ( 48 ), β-cell-enriched tissue ( 49 ), diabetic kidney ( 50 , 51 ), and diabetic peripheral neuropathy ( 52 ).…”
Section: Discussionsupporting
confidence: 87%
“…The absolute value of the binding energ indicates the affinity of the ligands with the target and the conformational stability. Th absolute value greater than 4.25 kcal/mol, 5.0 kcal/mol, and 7.0 kcal/mol indicates certain, good and strong binding activity, respectively [10]. The molecular docking resul showed that the binding ability of all DMU-212 metabolites to BSHs was stronger, and th absolute values of the binding energy of each active component were stronger than th of DMU-212 (7.0 kcal/mol).…”
Section: Molecular Dockingmentioning
confidence: 96%